2017
DOI: 10.1363/43e4417
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perceptions of Emergency Contraceptive Pills Among Women in Kinshasa, Democratic Republic of the Congo

Abstract: Emergency contraceptive pills have the potential to address gaps in the family planning method mix in the DRC. Assessing whether women have incomplete or erroneous information about family planning methods can provide better understanding of women's contraceptive choices in low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…Another quantitative survey showed that the majority (54%) of unmarried sexually active youth did not use contraception because they were not married [ 25 ]. A qualitative study in the DRC among women aged 15–35 years revealed that women frequently used deworming or anti-malarial medicines after sex as a form of emergency contraception [ 26 ]. Similar to young people in our study, qualitative research from Eastern DRC among adults yielded highly similar results to the current study on SRH themes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another quantitative survey showed that the majority (54%) of unmarried sexually active youth did not use contraception because they were not married [ 25 ]. A qualitative study in the DRC among women aged 15–35 years revealed that women frequently used deworming or anti-malarial medicines after sex as a form of emergency contraception [ 26 ]. Similar to young people in our study, qualitative research from Eastern DRC among adults yielded highly similar results to the current study on SRH themes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change should be complemented by the expansion of the method mix offered by CBDs, which in AcQual 3 will include DMPA-SC (Sayana Press) and emergency contraceptive pills, both in high demand and retailed at higher prices than other community-level methods. The addition of these 2 methods to the CBDs' method mix stems from separate Tulane-led research outlining the opportunities for community-based provision of these methods, 16 , 17 and illustrate how pilot studies and operational research (such as this process evaluation) can be leveraged to improve program design and implementation 18 …”
Section: Discussion and Resulting Changes To The Acqual Modelmentioning
confidence: 99%
“…Levamisole, which is a drug normally indicated against roundworms, is commonly used among youth in Kinshasa as a contraceptive in 70.2% of self-medication cases; it is used after unprotected intercourse to prevent an unwanted pregnancy [5,6]. The mechanism of action used for this drug is not known but its use is motivated by the fact that this drug is contraindicated in pregnancy, leading girls to believe that this drug can be used as an abortifacient.…”
Section: Levamisole Tabletmentioning
confidence: 99%
“…The mechanism of action used for this drug is not known but its use is motivated by the fact that this drug is contraindicated in pregnancy, leading girls to believe that this drug can be used as an abortifacient. In 75.9% of selfmedication cases, the doses used are higher than the usual doses, increasing by this way the health risk of intoxication [5,15].…”
Section: Levamisole Tabletmentioning
confidence: 99%
See 1 more Smart Citation